2017
DOI: 10.3389/fpsyg.2017.00668
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Insider Status and Feedback Reactions: A Dual Path of Feedback Motivation Attribution

Abstract: Many studies have evaluated how the characteristics of feedback receiver, feedback deliverer and feedback information influence psychological feedback reactions of the feedback receiver while largely neglecting that feedback intervention is a kind of social interaction process. To address this issue, this study proposes that employees’ perceived insider status (PIS), as a kind of employee-organization relationship, could also influence employees’ reactions to supervisory feedback. In particular, this study inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 57 publications
0
15
0
Order By: Relevance
“…The two wave data collecting method was utilized to avoid bias of the results from self-reported data (e.g., Xiao et al, 2017). The survey was initially conducted from October to December of 2018 and second data collection was conducted during August 2019.…”
Section: Methodsmentioning
confidence: 99%
“…The two wave data collecting method was utilized to avoid bias of the results from self-reported data (e.g., Xiao et al, 2017). The survey was initially conducted from October to December of 2018 and second data collection was conducted during August 2019.…”
Section: Methodsmentioning
confidence: 99%
“…Although some recent studies have found that perceived insider status as belongingness will increase employees’ trust in the organization, they also did not clarify the reciprocal relationship between trust and perceived insider status ( Knapp et al, 2019 ). research also suggests that managerial feedback to employees positively develops their perception of being insiders ( Chen et al, 2017 ). Based on the above synthesis, this study hypothesizes that:…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…Leaders can use incentives such as benefits, empowerment (Chen and Aryee, 2007), training or promotions to send signals (Stamper et al , 2009). Then, employees will perceive spiritual and material differences to judge whether they have achieved insider status (Chen et al , 2017).…”
Section: Theory and Hypotheses Developmentmentioning
confidence: 99%